Digitalisasi Industri Kecil Dan Produk Pertanian Daerah Upaya Untuk Pemberdayaan Masyarakat Di Desa Karangbendo Kecamatan Rogojampi Kabupaten Banyuwangi - Achmad As'ad Sonief (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2019)
Rural development is highly demanded to play a more intensive role, in order to catch up from other regions in Indonesia and face global competition. Micro, Small and Medium Enterprises (MSMEs) become an important role in development in Indonesia. Karangbendo village produces many products of industrial people and agroindustry products, especially batik which is a local wealth in everyday life is still conventional in the field of product marketing. The era of information technology cannot be dammed to progress, many fields have been utilizing information technology to develop its business. This activity aims to empower the community through digitalization of UMKM. The results obtained are the website design of UMKM Karangbendo village that can be accessed through personal computers and mobile phones. The website design of UMKM with the address https://umkm-karangbendo.